Identifying Complementary and Alternative Medicine Usage Information from Internet Resources - Sharma, Vivekanand; Holmes, John H.; Sarkar, Indra N. (Methods of Information in Medicine, 2016)
Objectives: Identify and highlight research issues and methods used in studying Complementary and Alternative Medicine (CAM) information needs, access, and exchange over the Internet.Methods: A literature search was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines from PubMed to identify articles that have studied Internet use in the CAM context. Additional searches were conducted at Nature.com and Google Scholar.Results: The Internet provides a major medium for attaining CAM information and can also serve as an avenue for conducting CAM related surveys. Based on the literature analyzed in this review, there seems to be significant interest in developing methodologies for identifying CAM treatments, including the analysis of search query data and social media platform discussions. Several studies have also underscored the challenges in developing approaches for identifying the reliability of CAM-related information on the Internet, which may not be supported with reliable sources. The overall findings of this review suggest that there are opportunities for developing approaches for making available accurate information and developing ways to restrict the spread and sale of potentially harmful CAM products and information.Conclusions: Advances in Internet research are yet to be used in context of understanding CAM prevalence and perspectives. Such approaches may provide valuable insights into the current trends and needs in context of CAM use and spread.
Keywords: Internet; complementary therapies; informatics